2019
DOI: 10.1590/s1983-41952019000500003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear static analysis of a pile-supported wharf

Abstract: The aim of this paper is to carry out a nonlinear static analysis using a case study of a pile-supported wharf in a new oil tankers port. The seismic activity in this area is very intense with the peak ground acceleration of 0.55 g; for this reason, it is very important to analyse the structural behaviour of the nonlinear situation. The analysis of the wharf, modelled in 3D by finite element method, serves to calculate the structure vibration periods (the structure’s first period is 1.68 s) and the capacity cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The case study is a real PSWS in a port located at the Northern of Venezuela 25 . The structure has an area of 6,520 m 2 where the length of the wharf in the transversal direction is 40 m and in the longitudinal direction—parallel to the sea—is 163 m. The deck of the wharf is formed by reinforced transversal beams with height of 1.95 m and a concrete slab with average thickness of 0.85 m. The wharf level is 3.40 m above the mean sea level, with a minimum and maximum flood of −0.40 and +0.875 m, respectively.…”
Section: Description Of the Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The case study is a real PSWS in a port located at the Northern of Venezuela 25 . The structure has an area of 6,520 m 2 where the length of the wharf in the transversal direction is 40 m and in the longitudinal direction—parallel to the sea—is 163 m. The deck of the wharf is formed by reinforced transversal beams with height of 1.95 m and a concrete slab with average thickness of 0.85 m. The wharf level is 3.40 m above the mean sea level, with a minimum and maximum flood of −0.40 and +0.875 m, respectively.…”
Section: Description Of the Structurementioning
confidence: 99%
“…Studies about PSWSs are more limited, 24–28 probably due to the fact that the construction of ports is less frequent than other structures, they are more expensive, it is more complicated to establish concrete plans between companies and governments. Moreover, to design this type of structures more elevate competence of the designer is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear simulation must be employed in the seismic analysis of the response of PSWs to massive earthquakes. Pushover analysis is a reliable and effective approach for observing the inelastic behavior, seismic load capacity, and plastic hinge formation of PSWs [8]. In addition, PSW serviceability (i.e., displacement and crack width limitations) plays a vital role in these designs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the seismic performance of a wharf based on the acceptance criteria outlined in ASCE 61-14. Such studies have been conducted by Hanifah et al (2017); Bergman et al (2016); Palma-ochoa and Vasquez (2019); Su et al (2021), while Venkatalakshmi et al (2017) and Zacchei et al (2019) used the acceptance criteria of Applied Technology Council, ATC-40 (1996) as a reference. Bruin et al (2016); Goel and Goel (2017); Goel (2018), and Sandoval et al (2019) have also reported that the substitute structure method for determining the target displacement based on ASCE 61-14 produces overestimated and underestimated results on structures with short and longer periods respectively.…”
Section: Introductionmentioning
confidence: 99%